Using behavioral skills training and video rehearsal to teach blackjack skills. Issue 3 (14th July 2015) - Speelman, Ryan C.; Whiting, Seth W.; Dixon, Mark R.
<x xml:space="preserve">Abstract</x> A behavioral skills training procedure that consisted of video instructions, video rehearsal, and video testing was used to teach 4 recreational gamblers a specific skill in playing blackjack (sometimes called card counting). A multiple baseline design was used to evaluate intervention effects on card‐counting accuracy and chips won or lost across participants. Before training, no participant counted cards accurately. Each participant completed all phases of the training protocol, counting cards fluently with 100% accuracy during changing speed criterion training exercises. Generalization probes were conducted while participants played blackjack in a mock casino following each training phase. Afterwards, all 4 participants were able to count cards while they played blackjack. In conjunction with count accuracy, total winnings were tracked to determine the monetary advantages associated with counting cards. After losing money during baseline, 3 of 4 participants won a substantial amount of money playing blackjack after the intervention.